Humoral signatures of protective and pathological SARS-CoV-2 infection in children - Bartsch, Yannic C.; Wang, Chuangqi; Zohar, Tomer; Fischinger, Stephanie; Atyeo, Caroline; Burke, John S.; Kang, Jaewon; Edlow, Andrea G.; Fasano, Alessio; Baden, Lindsey R.; Nilles, Eric J.; Woolley, Ann E.; et al. (Nature medicine, 2021)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic continues to spread relentlessly, associated with a high frequency of respiratory failure and mortality. Children experience largely asymptomatic disease, with rare reports of multisystem inflammatory syndrome in children (MIS-C). Identifying immune mechanisms that result in these disparate clinical phenotypes in children could provide critical insights into coronavirus disease 2019 (COVID-19) pathogenesis. Using systems serology, in this study we observed in 25 children with acute mild COVID-19 a functional phagocyte and complement-activating IgG response to SARS-CoV-2, similar to the acute responses generated in adults with mild disease. Conversely, IgA and neutrophil responses were significantly expanded in adults with severe disease. Moreover, weeks after the resolution of SARS-CoV-2 infection, children who develop MIS-C maintained highly inflammatory monocyte-activating SARS-CoV-2 IgG antibodies, distinguishable from acute disease in children but with antibody levels similar to those in convalescent adults. Collectively, these data provide unique insights into the potential mechanisms of IgG and IgA that might underlie differential disease severity as well as unexpected complications in children infected with SARS-CoV-2. A study of multisystem inflammatory syndrome in children (MIS-C) shows maintenance of elevated levels of monocyte-activating pathogen-specific IgG not seen in children infected with SARS-CoV-2 who do not develop MIS-C.